Deep brain stimulation of the nucleus accumbens for the treatment of addiction. (10th December 2012) - Müller, Ulf J.; Voges, Jürgen; Steiner, Johann; Galazky, Imke; Heinze, Hans‐Jochen; Möller, Michaela; Pisapia, Jared; Halpern, Casey; Caplan, Arthur; Bogerts, Bernhard; Kuhn, Jens
Abstract : Despite novel medications and other therapeutic strategies, addiction to psychotropic substances remains one of the most serious public health problems worldwide. In this review, beginning with an introduction of deep brain stimulation (DBS), we highlight the importance of the nucleus accumbens (NAc) in the context of the reward circuitry and addictive behavior. We will provide a short historic overview of other neurosurgical approaches to treat addiction and describe the experimental and preclinical data on DBS in addiction. Finally, we call attention to key ethical issues related to using DBS to treat addiction that are important for future research and the design of clinical trials.